Comparative Proteomic, Physiological, Morphological, and Biochemical Analyses Reveal the Characteristics of the Diploid Spermatozoa of Allotetraploid Hybrids of Red Crucian Carp (Carassius auratus) and Common Carp (Cyprinus carpio). Issue 2 (1st February 2016) - Duan, Wei; Xu, Kang; Hu, Fangzhou; Zhang, Yi; Wen, Ming; Wang, Jing; Tao, Min; Luo, Kaikun; Zhao, Rurong; Qin, Qinbo; Zhang, Chun; Liu, Jinhui; et al.
Abstract: The generation of diploid spermatozoa is essential for the continuity of tetraploid lineages. The DNA content of diploid spermatozoa from allotetraploid hybrids of red crucian carp and common carp was nearly twice as great as that of haploid spermatozoa from common carp, and the durations of rapid and slow progressive motility were longer. We performed comparative proteomic analyses to measure variations in protein composition between diploid and haploid spermatozoa. Using two-dimensional electrophoresis followed by liquid chromatography tandem mass spectrometry, 21 protein spots that changed in abundance were analyzed. As the common carp and the allotetraploid hybrids are not fully sequenced organisms, we identified proteins by Mascot searching against the National Center for Biotechnology Information non-redundant (NR) protein database for the zebrafish ( Danio rerio ), and verified them against predicted homologous proteins derived from transcriptomes of the testis. Twenty protein spots were identified successfully, belonging to four gene ontogeny categories: cytoskeleton, energy metabolism, the ubiquitin-proteasome system, and other functions, indicating that these might be associated with the variation in diploid spermatozoa. This categorization of variations in protein composition in diploid spermatozoa will provide new perspectives on male polyploidy. Moreover, our approach indicates that transcriptome data are useful for proteomic analyses in organisms lacking full protein sequences.